2001
DOI: 10.1364/oe.8.000263
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous imaging and optode calibration with diffuse optical tomography

Abstract: In order for diffuse optical tomography to realize its potential of obtaining quantitative images of spatially varying optical properties within random media, several potential experimental systematic errors must be overcome. One of these errors is the calibration of the emitter strength and detector efficiency/gain. While in principle these parameters can be determined accurately prior to an imaging experiment, slight fluctuations will cause significant image artifacts. For this reason, it is necessary to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 21 publications
0
93
0
Order By: Relevance
“…Recent advances, such as inclusion of coupling errors as a part of reconstruction scheme by making them as unknowns and iteratively solving for them along with optical parameters, are possible. [34][35][36][37] But this makes the reconstruction problem more computationally complex in nature as the number of unknowns of this procedure are larger than the techniques considered here. As the main focus of this article is about presenting a computationally efficient algorithm for reconstructing optical parameters, this issue was not considered as a part of this work.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances, such as inclusion of coupling errors as a part of reconstruction scheme by making them as unknowns and iteratively solving for them along with optical parameters, are possible. [34][35][36][37] But this makes the reconstruction problem more computationally complex in nature as the number of unknowns of this procedure are larger than the techniques considered here. As the main focus of this article is about presenting a computationally efficient algorithm for reconstructing optical parameters, this issue was not considered as a part of this work.…”
Section: Discussionmentioning
confidence: 99%
“…42; with extensive calibration, ref. 43). The other major difficulty arises because the distance from the maternal abdomen to the fetal brain is 2-4 cm (19) in humans.…”
Section: Discussionmentioning
confidence: 99%
“…For clinical data, we have found that, under compression, there are sufficient differences between our measurements and our model, even after calibration with a homogeneous phantom, that additional calibration parameters, one for each source and detector, must be introduced into the reconstruction (Boas et al 2001, Oh et al 2002. Thus, we make use of the following cost function: where s m and d n are source and detector amplitude calibration coefficients, respectively.…”
Section: Forward Model Cost Functions and Sensitivitiesmentioning
confidence: 99%